2022
DOI: 10.30541/v49i4iipp.771-798
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Climate Change on the Agricultural Sector of Punjab

Abstract: As back as the Industrial Revolution, anthropogenic activities namely, power generation from fossil fuels and deforestation activities have been continuously increasing the atmospheric concentration of GHGs beyond their natural limits resulting in an enhanced greenhouse effect, vis-à-vis, an increase in global temperature. The rise in temperature could be coupled with changes in rainfall pattern, rise in sea level, and frequency and severity of extreme events namely, cyclone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 24 publications
2
28
0
3
Order By: Relevance
“…Similarly in Pakistan, the scope of research linking climate change to agriculture is very restricted (TFCC, 2010). To date, studies on climate change and agriculture in Pakistan have been entirely limited to impacts of climate change on particular crops or sectors (Nomman and Schmitz, 2011;Hussain and Mudasser, 2007;Hanif et al, 2010;Ashfaq et al, 2011). None of the studies considered farmers' perspectives of climate change adaptation.…”
mentioning
confidence: 99%
“…Similarly in Pakistan, the scope of research linking climate change to agriculture is very restricted (TFCC, 2010). To date, studies on climate change and agriculture in Pakistan have been entirely limited to impacts of climate change on particular crops or sectors (Nomman and Schmitz, 2011;Hussain and Mudasser, 2007;Hanif et al, 2010;Ashfaq et al, 2011). None of the studies considered farmers' perspectives of climate change adaptation.…”
mentioning
confidence: 99%
“…More specifically, 1 0 C increase in Tm increases rice, sugarcane, cotton and wheat yield by 38.35 kgs/hect, 1152.59 kgs/hect, 1.64 kgs/hect and 92.1 kgs/hect respectively. Hanif, et al (2010) also found that increase in Rabi mean maximum temperature increased wheat yield in Punjab because wheat crop need heat for maturation. The results further show that maize yield is negatively related to Tm i.e.…”
Section: Climate Yield Relationship In Northern Irrigated Plain a (Zomentioning
confidence: 89%
“…Modified precipitation patterns result water scarcity and droughts and creates stress for crops and livestock. Storm, drought and floods, induced by climate change, are potential threats to humans and other living organisms [6]. Pakistan is highly vulnerable to climate variability and extremes.…”
mentioning
confidence: 99%